Morfologia e propriedades estruturais de óxidos metálicos complexos: um enfoque teórico e experimental - Oliveira, Marisa Carvalho de (2018)
Design, control and direct characterization of the properties of the surfaces are prerequisites for all practical applications of (nano) materials. Within this context, the present doctoral thesis is an experimental and theoretical work on the morphology, structure, electronic and optical properties of materials based on complex metal oxides: BaWO4, BaMoO4, solid solution BaW1-xMoxO4 (x= 0, 0.25, 0.50, 0.75 and 1), CaMoO4, ZnMoO4, ZnMoO4:Eu3+, CaZrO3 and CaZrO3:Eu3+, which constitute the systems studied in this Doctoral Thesis. In Chapter 1 of the introduction, we begin by highlighting the importance of combining theory, simulation and experiment in the study of materials, then we present a general view on the concept of morphology in particular, how to obtain it theoretically using Wulff's construction. Chapter 2 presents the theoretical methods and computational simulations, explaining how we characterize the excited electronic states and calculate the structural, electronic and optical properties. The motivations and objectives of this work are listed in Chapter 3. Chapter 4 presents, analyzes and discusses the obtained results, which were carried out in collaboration with the Center de Desenvolvimento de Materiais Funcionais (CDMF), at the Federal University of São Carlos (UFSCar) and in collaboration with the Laboratório de Síntese Química de Materiais (LSQM), in the Department of Matters of the Federal University of Rio Grande do Norte (UFRN), while The general conclusions are summarized in Chapter 5, along with the topics that could be the continuation of this work. Below is a summary, written in Portuguese, in order to comply with the regulations of the “co-tutela” agreement.